The Profile of Type 2 DM Patients with Insulin Resistance at Citra Husada Hospital - Rizki Eko Prasetyo (Pena Medika Jurnal Kesehatan, 2022)
Type 2 DM is a complex chronic multifactorial disease involving many organs. Insulin resistance in type 2 DM patients that occurs due to insulin deficiency or insulin defects can also occur due to metabolic syndrome. This study aims to determine the profile of type 2 DM patients with insulin resistance based on the characteristics of HbA1c levels, leukocyte levels, and hypertension status at Citra Husada Jember Hospital in 2022. This study used a descriptive method with a case series design. The population study consisted of 40 type 2 DM patients who underwent outpatient care in May 2022 using a total sampling technique. The results of the study showed the characteristics of type 2 DM patients with HbA1c levels > 6.5 (25%), 30% leukocytosis, and 45% hypertension. This condition continues even though blood glucose is controlled due to the phenomenon of metabolic memory. The addition of natural bioactive compounds in type 2 DM patients receiving metformin therapy can overcome metabolic memory.Keywords: Type 2 DM, metabolic memory, HbA1c, leukocyte, hypertension